Changes in the Complete Blood Counts Measurements of Gas Stations Workers in Eastern Libya - Saad Saleh Khagkhag; Mahmoud Ali Alhosni; Emad Aldin Mohammed Hassan (African Journal of Advanced Pure and Applied Sciences, 2024)
The adverse effects of daily exposure to benzene may be related to the inability of the hematopoietic system with bone marrow suppression, an increased hazard of blood cell morphology abnormality and creating cancer. Objective: To evaluate the complete blood count measurements among gasoline-exposed workers at foul station as compared to non-exposed controls in east Libya. Methods: This comparative cross-sectional study was conducted on 102 participants (exposed group) and 102 participants (unexposed group). Socio-demographic characteristics and duration of exposure information were collected employing a structured questionnaire. NIHON KOHDEN was utilized for hematological analysis. Data were entered and analyzed utilizing SPSS version 25. Results: Compared to the control group, the study`s mean red blood cell count, white blood cell count, hemoglobin level, hematocrit, and mean cell hemoglobin concentration of gas station employees showed a significant increase. Conversely, as compared to healthy controls, the mean cell volume (MCV), mean cell hemoglobin (MCH) value, and platelet count (PLT) of gas station employees showed a considerable decline. Additionally, there was a significant relation observed between mean cell hemoglobin, and red blood cell count was seen during the duration of exposure to gasoline. Conclusion: The majority of hematological parameters of petrol filling workers in this study showed an increase compared with healthy controls, this might be associated with exposure to petrol chemicals. However, further longitudinal studies with a larger sample size and advanced tests should be conducted to explore the impact of petrol exposure on hematopoiesis.